Statistical Application Training for Students for Thesis Preparation - Zahroh, Umy; Hartiningtyas, Lativa (CV. BImbingan Belajar Assyfa, 2023)
This research is motivated by the condition that many final-year students still need to complete their studies on time due to a lack of understanding about how to complete a thesis. One of the research approaches used to work on a thesis is quantitative. A quantitative approach is research that analyses data in the form of numbers and attempts to interpret the analysis results. This research uses a type of action research to provide training to final-year students in analyzing data assisted by statistical applications so that it can make it easier for students to complete their thesis. The results of this research are that students' understanding of quantitative data processing has increased compared to before the training was implemented. Students feel that this training can help them complete their thesis and graduate on time.